The Concept of Paññā in Buddhist Philosophy - Phoonaphiphat, Phramaha Banchong; (Cherdchai Sīlasampanno), Phrakittisarasuthee; Kotsombat, Samran (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 2 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
This article is regarding the importance of Paññā in Buddhist Philosophy. It is to understand the meaning of Paññā correctly. The systems of Buddhist philosophy emphasize on the concept of Paññā: Buddhist philosophy believes “Paññā is the most importance in human life. Without Paññā a person cannot know what he ought to do, what he ought not to do, and he cannot discriminate what thing has value and what thing has no value. There are the main concepts of Paññā in Buddhist philosophy as follows: (i) The meaning of Paññā is concerned the respective systems agree with each other that “Sammādiṭṭhi” is the principle of practice for the goal of Buddhist philosophy. As for the Nature of Paññā of Buddhist philosophy is clearly evident in line of truth of all nature that free from nescience (delusion) and craving (desire), entirely attain to salvetion which means Nibbāna. The points of Buddhist departure are of the view that “Nibbāna” is selfless (Anattā.) (ii) Buddhist philosophy is identical so far as the origin of epistemology or Paññā is concerned; the original source of epistemology of Buddhist philosophy is listening, reasoning, and practice (meditation). (iii) The Kinds of epistemology or Paññā to Buddhist philosophy is divided into two levels, namely, the common or worldly level which originated by sense – perception and the higher or ultimate one which is originated by insihgt development. (iv) The Principles of attaining liberation, Buddhist philosophy lays special emphasis on threefold Trining (Tri-sikkhā), namely, precept (Sīla), concentration (Samādhi), and Wisdom (Paññā).